Analysis of Alcohol and Cigarette Consumption in Children and Adolescents and Its Implications for Crime Prevention in Indonesia from a Criminological Perspective - Maria Minerva Gani; Jason Matthew Anthony; Nathasya Jhonray Siregar; Tasya Amira (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This article examines juvenile delinquency in the form of alcohol and tobacco consumption among children under 18 years old in Indonesia from both legal and criminological perspectives. Using a normative-empirical approach, this study analyzes statutory regulations alongside secondary data from institutions such as WHO and the Indonesian Ministry of Health. The findings indicate that early exposure to addictive substances functions as a criminogenic factor that increases the likelihood of future criminal behavior. Although Indonesia has established a comprehensive legal framework, including Law No. 35 of 2014 on Child Protection and Government Regulation No. 109 of 2012, weak enforcement and regulatory inconsistencies remain significant challenges. A comparative perspective with Singapore and Malaysia reveals that stricter enforcement and integrated preventive policies contribute to better outcomes. This study concludes that early intervention through legal, social, and structural approaches is essential to prevent the escalation of juvenile delinquency into criminal acts.